The Correlation Of Unsafe Action And Unsafe Condition On Work Accident Among Nurses At Dr Tadjuddin Chalid Hospital Makassar - Rindi Andika Yanti Pasambo; Hesti Hesti; Andi Alim; Abdul Gafur (Lambung Mangkurat University, 2023)
Nurses working in hospital settings face a heightened susceptibility to work-related accidents, which primarily stem from two underlying factors: unsafe behaviour and hazardous conditions. Work accident data at Dr Tadjuddin Chalid, there are 12 reported cases of work accidents in 2021. The objective of this study was to establish the correlation between unsafe actions, unsafe conditions, and the frequency of work accidents among nurses at Dr Tadjuddin Chalid Makassar Hospital. The research methodology employed for this investigation was observational, adopting a cross-sectional approach. The targeted population encompassed 205 individuals, with a final sample size of 136 nurses being involved in this research endeavour. The sample is taken using a simple random sampling method. Respondent data collection using a questionnaire. Data analysis used the chi-square test to see the relationship between independent variables, namely unsafe actions (perceptions, work experience, work stress, work shifts and supervision) and unsafe conditions (work environment, tools/materials and dangerous unsafe environment) with the occurrence of work accidents. The findings indicated a notable correlation between unsafe behaviour and work accidents (p-value = 0.001), alongside a significant relationship between unsafe conditions and work accidents (p-value = 0.007). In summation, it can be concluded that both unsafe behaviour and unsafe conditions are connected to the incidence of work accidents at Dr. Tadjuddin Chalid Makassar Hospital. It is recommended that the hospital emphasizes enhancing the work environment's conditions and elevating the quality of training and supervision. These measures are essential for mitigating the prevalence of work accidents among nurses.